Magnetic carbon xerogels for the catalytic wet peroxide oxidation of 4-nitrophenol solutions - Ribeiro, Rui (2015)
Catalytic wet peroxide oxidation (CWPO) is a well-known advanced oxidation process for the removal of organic pollutants from industrial process waters and wastewater. Specifically, CWPO employs hydrogen peroxide (H2O2) as oxidation source and a suitable catalyst to promote its decomposition via formation of hydroxyl radicals (HO•), which exhibit high oxidizing potential and serve as effective species in the destruction of a huge range of organic pollutants